FINANCIAL RATIO ANALYSIS IN ASSESSING THE FINANCIAL PERFORMANCE OF THE REGIONAL GOVERNMENT OF PEMALANG REGENCY - Kunta Dwi Pangestu; Nina Andriana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Local government performance is the most critical factor in the regional development process. Financial performance can be one of the indicators in assessing the performance of a local government. This study aims to evaluate the financial performance of the Pemalang Regency Government for 2018-2020 using regional financial ratio analysis. The financial ratios used include the regional financial independence ratio, effectiveness ratio, efficiency ratio, compatibility ratio, and growth ratio. The data collection method used in this research is the documentation method combined with the descriptive quantitative analysis method. The data used is the Pemalang Regency Financial Report which is downloaded through the official website of the Pemalang Regency Government. The results showed that the regional financial independence of the Pemalang Regency was still very low. However, the Pemalang Regency Government has been quite effective and efficient in managing its revenue. Meanwhile, the Pemalang Regency Government prioritizes using its funds for operating expenditures compared to capital expenditures. Furthermore, the calculation results of the growth ratio show that the revenue and expenditure growth of Pemalang Regency from 2018-2020 tends to fluctuate.